2015
DOI: 10.1007/s10008-015-2973-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole electrochemistry: a short review

Abstract: Carbazole and its derivatives have become important materials for optoelectronic applications in recent years. In this work, we have collated information on the oxidation of carbazole and its derivatives. Knowledge of their electrochemical properties affords insight into the mechanisms for their oxidation and reduction as well as possible subsequent reactions. This knowledge therefore provides the basis for evaluating the stabilities of these materials and for designing novel carbazole-derived materials with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
176
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(191 citation statements)
references
References 36 publications
15
176
0
Order By: Relevance
“…[45] The evolution of the CVs is even accentuated when cycling between 0.2 and 1.86 V( Figure 4C)w ith a complete disappearance of the first oxidation wave at 0.86 V, in favour of the appearance and the regular growth of an ew redox system centred at 1.5-1.3 V, and the covering of the electrode surface with an insoluble deposit. Although anodic coupling is aw ell-known technique to generate p-conjugated oligomers and polymers from various linear building blocks, [46,51,52] as far as we know, this strategy has never been used forn anorings. Although anodic coupling is aw ell-known technique to generate p-conjugated oligomers and polymers from various linear building blocks, [46,51,52] as far as we know, this strategy has never been used forn anorings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] The evolution of the CVs is even accentuated when cycling between 0.2 and 1.86 V( Figure 4C)w ith a complete disappearance of the first oxidation wave at 0.86 V, in favour of the appearance and the regular growth of an ew redox system centred at 1.5-1.3 V, and the covering of the electrode surface with an insoluble deposit. Although anodic coupling is aw ell-known technique to generate p-conjugated oligomers and polymers from various linear building blocks, [46,51,52] as far as we know, this strategy has never been used forn anorings. Although anodic coupling is aw ell-known technique to generate p-conjugated oligomers and polymers from various linear building blocks, [46,51,52] as far as we know, this strategy has never been used forn anorings.…”
Section: Resultsmentioning
confidence: 99%
“…Although anodic coupling is aw ell-known technique to generate p-conjugated oligomers and polymers from various linear building blocks, [46,51,52] as far as we know, this strategy has never been used forn anorings. [47][48][49][50][51][52][53] Firstly,t his particularity can be explained by the carbon atoms involved in the coupling.I ndeed, as previously shown with variousc arbazole oligomers or polymers, [46] such type of anodic couplings take place at the C3 and C6 carbon atoms (as forc lassical electrophilic aromatics ubstitutions), [54] which are both in meta position of the biphenyl linkagel eading to an electronic decoupling. The electrochemical behaviour of the electrodepositedm aterials tudied in as olutioni na bsence of any electroactives ubstance ( Figure 4D)s hows ar eversible redoxp rocess with am aximum at 1.5 Va nd E onset ox = 1.02 V( HOMO = À5.42 eV).…”
Section: Resultsmentioning
confidence: 99%
“…This feature will prevent an oxidative polymerization typical for carbazole derivatives and hence stabilize the charged redox states of the molecules. 37 5. Addition of thiophene -based linkers results in almost complete quenching of emission what might be caused by the stronger push-pull effect for systems with elongated conjugation framework.…”
Section: Resultsmentioning
confidence: 99%
“…33 Indeed, Siove and co-workers showed that a monomer in which two carbazole units are tethered by an N-substituted alkyl spacer merely leads to sequential dimerization upon chemical oxidation to form a polymer that could be spin-cast on electrodes. 34 The C–C coupling para to the nitrogen upon (electro)oxidation 2426 via a 4 electron ECCE process is analogous to the dimerization of indoline derivatives 35 and N , N -dialkyl substituted anilines, 3638 which occur readily.…”
Section: Introductionmentioning
confidence: 99%